IDENTIFIKASI HUBUNGAN FLUKTUASI NILAI SOI TERHADAP CURAH HUJAN BULANAN DI KAWASAN BATUKARU-BEDUGUL, BALI - As-syakur, Abd. Rahman (Bumi Lestari; Vol 7 No 2, 2012)
The issue dealing with climate changes has been becoming more stressed out along with more frequent of the occurrence of extreme weather as a consequence of anomaly climate. Examples of anomaly climate that often related to extreme weather are El Nino and La Nina. One of methods to find out the condition of El Nino and La Nina is by observing SOI values. Methods utilized in this research were by collecting rainfall data and SOI values along with regresion analyses to observe the determination coefficient values (R2). Results of this research showed that the rainfall variability on the research area did not affect fluctuations of SOI values on rainy seasons except in Munduk, while on dry seasons it was very clear shown, except in Gitgit. On the transition period, the influence of SOI values on rainfall variability was seen differ on every rain stations. On the first transition period (April), the fluctuation of SOI values had seen clearly being influenced on Baturiti’s rain station and was not influenced on Gitgit’s rain station. On the second transition (October), the influence of SOI values has affected Munduk rain station and did not influence that on Candikuning rain station. The research’s location that covered an area with monsoon rain paterns, the presence of Walker cycles, and ITCZ were also affected the results.The position of rain stations on a certain topography or location also influenced rainfall variability, so it can cause the difference on SOI values on each season.
Keywords: SOI value, rainfall, El Nino, La Nina